2010
DOI: 10.1103/physreve.81.066109
|View full text |Cite
|
Sign up to set email alerts
|

Generalized priority-queue network dynamics: Impact of team and hierarchy

Abstract: We study the effect of team and hierarchy on the waiting-time dynamics of priority-queue networks. To this end, we introduce generalized priority-queue network models incorporating interaction rules based on team-execution and hierarchy in decision making, respectively. It is numerically found that the waiting-time distribution exhibits a power law for long waiting times in both cases, yet with different exponents depending on the team size and the position of queue nodes in the hierarchy, respectively. The ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The pure priority selection mechanism can also be altered, e.g., to a hybrid priority-FCFS or priority-random selection mechanism. Finally, some kind of coupling between different queues is an important topic, for instance for modeling the interaction between (the tasks of) two people [24][25][26]. An analysis of a useful coupled model can be found in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…The pure priority selection mechanism can also be altered, e.g., to a hybrid priority-FCFS or priority-random selection mechanism. Finally, some kind of coupling between different queues is an important topic, for instance for modeling the interaction between (the tasks of) two people [24][25][26]. An analysis of a useful coupled model can be found in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…In these models, prioritization of tasks is considered a major cause of heavy-tailed nature of human dynamics. These models were extended to include interactions between two or more agents inevitable in social system [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…This also relates to the heavy-tailed temporal distributions observed in human and animal behavior and locomotion [1,2,3,4,5,6,14,15,16,17,18]. A number of approaches have been used to characterize the features of the empirical time statistics of written communication [6,19,20,21,22,23,11,24,25,26,27], with debated indications of scaling behavior for the waiting times, and for their possible modeling through priority queueing. A new method for the analysis of these human reactive phenomena has been recently proposed [13], through which it was shown that, in particular, the mechanisms underpinning the response-time (RT) statistics of written correspondence are best understood, rather than in terms of standard time t, in terms of an agent's activity, i.e.…”
Section: Introductionmentioning
confidence: 99%